A Comparative Investigation of Soil Fundamental Frequencies: A Case Study for İzmir Province - Ahu Kömeç Mutlu; Ülgen Mert Tuğsal; Musavver Didem Cambaz (Doğal Afetler ve Çevre Dergisi)
The earthquake (Mw 6.9) that occurred in the northern part of Samos Island and Doğanbey-İzmir offshore in the Aegean Sea at 14:51 local time on October 30, 2020 was felt in İzmir, Samos Island and many surrounding cities and settlements. Considering the earthquake intensity map, contrary to what is expected, the highest impact occurred in Bayraklı district, which is 70 km away from the epicenter, and caused not only severe structural damage but also fatalities in the region. When the structural damages are evaluated, determining the local soil properties has an important place in the studies to predict the effects of a possible earthquake. The HVSR (Horizontal Vertical Spectral Ratio) method provides an advantage in determining the soil fundamental frequency and the soil amplification factor in the event of an earthquake, in that it can be widely used even in the seismically in-active regions. In this study, it is not only aimed to analyze the earthquake and ambient noise data obtained from the accelerometer and velocity stations but also to compare the results obtained by using HVSR method utilizing different softwares. Furthermore, response spectra were obtained for different local soil classes by using the data of the same stations and they are given in comparison with the design spectra included in the earthquake code. As a result of the study, it has been observed that the results obtained by the HVSR method are in good correlation with the soil effects in the region and the consequential structural damages. These examples illustrate HVSRpy’s commitment to exactly reproduce the results of GEOPSY, wherever the processing parameters and functionality of HVSRpy and GEOPSY overlap. This was done to allow users to check HVSRpy and to encourage standardization in HVSR processing.